Dynamic thiol/disulphide balance in patients undergoing hypotensive anesthesia in elective septoplasties. Issue 11 (18th September 2021) - Kazancioglu, Leyla; Batcik, Sule; Arpa, Medeni; Erdivanli, Basar; Ozergin Coskun, Zerrin; Celebi Erdivanli, Ozlem; Bahceci, Ilkay; Kazdal, Hizir; Erel, Ozcan; Neselioglu, Salim
Abstract: Objective: We aimed to investigate the effects of hypotensive anaesthesia on oxidative stress with serum thiol/disulphide balance in patients undergoing elective septoplasty procedures under general anaesthesia. Methods: Seventy‐two patients between the ages of 18‐60, with a physical condition I –II, according to the American Society of Anesthesiologists, were included in this prospective observational study. Septoplasty was chosen for standard surgical stress. According to the maintenance of anaesthesia, patients were divided into the groups as Hypotensive Anaesthesia (n = 40) and Normotensive Anaesthesia (n = 32). Serum thiol/disulphide levels were measured by the method developed by Erel & Neşelioğlu. Results: The native thiol and total thiol values of both groups measured at the 60th min intraoperatively were significantly lower than the preoperative values (both P  < .01). Intraoperatively, at the 60th min, there was no significant difference in terms of post‐native thiol and post‐total thiol levels between hypotensive and normotensive anaesthesia groups ( P  = .68 and .81, respectively). Age >40 years and female gender were found to have a significant effect on dynamic oxidative stress ( P  = .002 and .001, respectively). Conclusion: This pilot study has found that hypotensive anaesthesia had no adverse effect on dynamic thiol/disulphide balance in elective surgeries.